THORAKOSKOPIE: DIAGNOSTISCHE UND THERAPEUTISCHE INDIKATIONEN - Engel, Genady (Biomedical papers, 1998)
This survey is a comprehensive review of the diagnostic and therapeutic indication for thoracoscopy.
Keywords: Thoracoscopy / Indications / Contraindications / Technique